2021
DOI: 10.1007/s12649-021-01368-3
|View full text |Cite
|
Sign up to set email alerts
|

Linking Phosphorus Extraction from Different Types of Biomass Incineration Ash to Ash Mineralogy, Ash Composition and Chemical Characteristics of Various Types of Extraction Liquids

Abstract: Phosphorus (P) rich ash from biomass incineration is a potential promising alternative for non-renewable phosphate rock. This study considered the P recovery potential of poultry manure ash, sewage sludge ash and meat and bone meal ash through wet chemical extraction. XRD analysis showed that these three ash types had a distinct P mineralogy. If inorganic acids were used for the extraction, the P extraction efficiency was not or only slightly affected by the P mineralogy. Contrarily, for the organic acids, alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
(114 reference statements)
0
9
0
Order By: Relevance
“…In this study, P was extracted with 2% citric acid, yielding similar values for gBM ash (96.8%) as for TSP (98.0%), while cBM ash (85%), gB ash (78%) and cB ash (49%) contained less extractable P (% of P from total P; Figure 1B). This extractability of P was higher than in 0.5 M HCl, probably due to complexing agents in citric acid (Herzel et al, 2020;Luyckx et al, 2021). The lowest amount of P extracted with 2% citric acid was measured in cBS ash (30%; Figure 1B).…”
Section: Phosphorus Extractability From Bagassebased Ashesmentioning
confidence: 86%
“…In this study, P was extracted with 2% citric acid, yielding similar values for gBM ash (96.8%) as for TSP (98.0%), while cBM ash (85%), gB ash (78%) and cB ash (49%) contained less extractable P (% of P from total P; Figure 1B). This extractability of P was higher than in 0.5 M HCl, probably due to complexing agents in citric acid (Herzel et al, 2020;Luyckx et al, 2021). The lowest amount of P extracted with 2% citric acid was measured in cBS ash (30%; Figure 1B).…”
Section: Phosphorus Extractability From Bagassebased Ashesmentioning
confidence: 86%
“…Figure 3 shows that the P extraction efficiency with sodium hydroxide gradually decreased with increasing incineration temperature, which is related to the decreasing mass fraction of Al/Fe-phosphates in the SSA (see Figure 2). In general, Al-and/or Fe-phosphates dissolve well in alkaline extraction liquids such as sodium hydroxide, whereas Caphosphates do almost not dissolve in alkaline environment [14,30,54,55]. However, the P extraction efficiency with sodium hydroxide was generally lower than the mass fraction of Al/Fe-phosphates in the SSA samples obtained from the SMT protocol.…”
Section: P Extractionmentioning
confidence: 96%
“…Hydrochloric acid was selected because it is available on an industrial scale, and upon extraction, no additional solid residue is formed, only the ash extraction residue remains. Sodium hydroxide was selected because previous work showed that it co-extracts less heavy metals during P extraction compared to the beforementioned acids [13,14,29,30]. The experiments were carried out at the optimal extraction conditions determined in previous work of the authors [13]: sulfuric acid, hydrochloric acid and oxalic acid were applied at a concentration of 0.5 N, an L/S ratio of 10 ml/g ash and a contact time of 2 h; sodium hydroxide was applied at a concentration of 0.5 N, an L/S ratio of 50 ml/g ash and a contact time of 2 h.…”
Section: Extraction Experimentsmentioning
confidence: 99%
See 2 more Smart Citations